Operant conditioning of a spinal reflex can improve locomotion after spinal cord injury in humans. - Thompson, Aiko K.; Pomerantz, Ferne R.; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2013)
Operant conditioning protocols can modify the activity of specific spinal cord pathways and can thereby affect behaviors that use these pathways. To explore the therapeutic application of these protocols, we studied the impact of down-conditioning the soleus H-reflex in people with impaired locomotion caused by chronic incomplete spinal cord injury. After a baseline period in which soleus H-reflex size was measured and locomotion was assessed, subjects completed either 30 H-reflex down-conditioning sessions (DC subjects) or 30 sessions in which the H-reflex was simply measured [unconditioned (UC) subjects], and locomotion was reassessed. Over the 30 sessions, the soleus H-reflex decreased in two-thirds of the DC subjects (a success rate similar to that in normal subjects) and remained smaller several months later. In these subjects, locomotion became faster and more symmetrical, and the modulation of EMG activity across the step cycle increased bilaterally. Furthermore, beginning about halfway through the conditioning sessions, all of these subjects commented spontaneously that they were walking faster and farther in their daily lives, and several noted less clonus, easier stepping, and/or other improvements. The H-reflex did not decrease in the other DC subjects or in any of the UC subjects; and their locomotion did not improve. These results suggest that reflex-conditioning protocols can enhance recovery of function after incomplete spinal cord injuries and possibly in other disorders as well. Because they are able to target specific spinal pathways, these protocols could be designed to address each individual's particular deficits, and might thereby complement other rehabilitation methods.
Keywords: Learning; Locomotion; operant conditioning; plasticity; Rehabilitation; spasticity